1998
DOI: 10.1128/mcb.18.11.6399
|View full text |Cite|
|
Sign up to set email alerts
|

The Middle Subunit of Replication Protein A Contacts Growing RNA-DNA Primers in Replicating Simian Virus 40 Chromosomes

Abstract: The eukaryotic single-stranded DNA binding protein replication protein A (RPA) participates in major DNA transactions. RPA also interacts through its middle subunit (Rpa2) with regulators of the cell division cycle and of the response to DNA damage. A specific contact between Rpa2 and nascent simian virus 40 DNA was revealed by in situ UV cross-linking. The dynamic attributes of the cross-linked DNA, namely, its size distribution, RNA primer content, and replication fork polarity, were determined. These data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 69 publications
2
46
0
Order By: Relevance
“…2). In agreement with other studies which employed different DNA-protein cross-linking agents, both RPA70 and RPA32 were cross-linked to DNA (18,21,31). Importantly, neither XPA nor XPC, DNA binding proteins with some affinity for damaged DNA, were cross-linked to psoralen.…”
Section: Resultssupporting
confidence: 89%
“…2). In agreement with other studies which employed different DNA-protein cross-linking agents, both RPA70 and RPA32 were cross-linked to DNA (18,21,31). Importantly, neither XPA nor XPC, DNA binding proteins with some affinity for damaged DNA, were cross-linked to psoralen.…”
Section: Resultssupporting
confidence: 89%
“…RPA participates in the synthesis and processing of Okazaki fragments during DNA replication in viruses and in yeast (Mass et al, 1998;Bae et al, 2001). In multicellular organisms, however, its participation in the preinitiation complex is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Once a 3Ј-NT-5Ј or 3Ј-NTT-5Ј initiation signal is encountered by the Pol ␣-primase complex, synthesis of a primer-RNA/DNA molecule is initiated. Previous studies indicate that RPA(HSSB) (87), particularly the 32-kDa subunit, is also required for the synthesis of primer-RNA/DNA (47,50) and for coordinating a Pol switch with Pol ␦ (76,92). Based on observations made in prokaryotic (30) and human systems (92), it is proposed that the synthesis of the origin proximal primer-RNA/DNA molecules is a prerequisite for the recruitment of RFC, PCNA, and Pol ␦ and the subsequent initiation of leading-strand synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that the Pol ␣-primase complex initiates DNA replication by synthesizing a small RNA/DNA hybrid that has been termed primer-RNA/DNA (16,(56)(57)(58). Primer-RNA/DNA is formed exclusively from lagging-strand DNA templates, initially in the vicinity of the SV40 origin and, at later stages of synthesis, at progressively distal locations (13,25,50). Once synthesized, primer-RNA/DNA molecules are extended by a second PCNA-dependent polymerase to form full-length Okazaki fragments (16,(56)(57)(58)78).…”
mentioning
confidence: 99%